Ulmus laevis in the iberian peninsula: A review of its ecology and conservation - Venturas, Martín; Fuentes Utrilla, Pablo; López, Rosana; Perea, Ramón; Fernández, Victoria; Gascó, Antonio; Guzmán, Paula; Li, Meng; Rodríguez Calcerrada, Jesús; Miranda, Eva; Domínguez, Jorge; González Gordaliza, Guillermo; et al. (SISEF - Italian Society of Silviculture and Forest Ecology, 2014)
European white elm (Ulmus laevis Pallas) populations are scarce,small and fragmented in the Iberian Peninsula. Due to these characteristics the indigenous status of the species in the region has been questioned,whilst the species’ role in Iberian riparian forest ecology has been neglected. Herein we review past studies regarding this species’ distribution and ecology in the Iberian Peninsula,with special emphasis on the establishment of conservation priorities. We first present a collection of palaeogeographic,historic and genetic data suggesting that the Iberian Peninsula was a glacial refuge for U. laevis. Secondly,we analyse U. laevis distribution in relation to soil physicochemical properties and water availability in Spain. Following this,we focus on the reproductive biology of the species,and investigate the effect of masting and empty seed production on predation and regeneration establishment. Finally,based on this knowledge,we propose conservation policies for U. Laevis in the Iberian Peninsula. ©Martin Venturas (martin.venturas@upm.es)
Keywords: Ulmus laevis; ODS 15 - Vida de ecosistemas terrestres